2022
DOI: 10.1101/2022.08.04.502794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cryptic transactivation domain of EZH2 binds AR and AR’s splice variant promoting oncogene activation and tumorous transformation

Abstract: Enhancer of Zeste Homolog 2 (EZH2) and androgen receptor (AR) are crucial chromatin regulators involved in the development and/or progression of prostate tumor, including advanced castration-resistant prostate cancer (CRPC). To sustain prostate tumorigenicity, EZH2 establishes noncanonical biochemical interaction with AR for mediating oncogene activation, in addition to its canonical role as a transcriptional repressor and enzymatic subunit of Polycomb Repressive Complex 2 (PRC2). However, the molecular basis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Treating with an EZH2 inhibitor also drastically reduced the number of called FLAG-βcatenin peaks in both EV and PTEN KD cells. These findings are consistent with other findings in which EZH2 induced the binding of AR, cMyc, and P300 to the chromatin to mediate gene expression (34,35). While previous studies suggest that EZH2 methylation of other non-histone proteins leads exclusively to gene activation or repression (19,20), our findings propose a model in which EZH2-mediated β-catenin methylation increases β-catenin's binding to the chromatin and fine-tunes β-catenin activity to both repress and activate gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…Treating with an EZH2 inhibitor also drastically reduced the number of called FLAG-βcatenin peaks in both EV and PTEN KD cells. These findings are consistent with other findings in which EZH2 induced the binding of AR, cMyc, and P300 to the chromatin to mediate gene expression (34,35). While previous studies suggest that EZH2 methylation of other non-histone proteins leads exclusively to gene activation or repression (19,20), our findings propose a model in which EZH2-mediated β-catenin methylation increases β-catenin's binding to the chromatin and fine-tunes β-catenin activity to both repress and activate gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that nucleolar AR-V7 staining was positive in 44% of CRPC samples, compared with 9% in human nucleus pulposus cell and 0 in benign tumor samples. This study further evaluated the predictive value of AR-V7, finding that high levels of AR-V7 cytoplasmic staining were associated with a greater risk of PSA recurrence after radical prostatectomy [36]. These results suggest that AR splicing variants are significantly higher in CRPC than human nucleus pulposus cells, and their high expression is closely related to castrationresistant formation and progression of CRPC.…”
Section: Ar Splicing Variantsmentioning
confidence: 85%